Implicature Analysis on Women’s Resistance in The Novel “The Years of the Voiceless” by Okky Madasari - Dien Afni Ariyati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to describe: (1) the meaning of utterances containing conventional implicatures in the novel ‘The Years of The Voiceless’ by Okky Madasari, (2) define the function of utterances containing conventional implicatures in the novel ‘The Years of The Voiceless’ by Okky Madasari, and (3) describe the types of utterances containing conventional implicatures in the ‘The Years of The Voiceless’ by Okky Madasari based on Grice’s theory about implicature. The research method was descriptive qualitative method. The data in this study are sentences in utterances containing implicature. The data in this study were obtained by reading, recording and note-taking techniques. The findings are as follows. There are 8 forms of conventional implicature found. Based on the results of the classification that has been done, there are four intentions, 1 utterance of the intention of commanding, 1 utterance of the intention of pride, 1 utterance of the intention of giving information. Types of utterances that contain conventional implicatures in the novel 'The Years of The Voiceless'. Each implicature has a function. The function of conventional implicatures in the novel can be categorized into three functions, namely 1. implicatures that function as persuasive or persuade, 1 implicature that functions as directive, namely giving advice, 1 implicature that functions as expressive, namely showing hatred. Based on the results of the classification that has been done, there are two classifications, 1 type of declarative speech (statement), 1 type of imperative speech (command).